Effect of povidone iodine, chlorhexidine digluconate and toyocamycin on amphizoic amoebic strains, infectious agents of Acanthamoeba keratitis – a growing threat to human health worldwide - Marcin Padzik; Wanda Baltaza; David Bruce Conn; Jacek P. Szaflik; Lidia Chomicz (Annals of Agricultural and Environmental Medicine, 2018)
Introduction Free-living amoebae, ubiquitous in outer environments, in predisposing circumstances may exist as parasites, infectious agents of Acanthamoeba keratitis. In recent decades, the vision-threatening corneal infection is a growing human health threat worldwide, including Poland. The applied therapy is often ineffective due to diagnostic mistakes, various pathogenicity of Acanthamoeba strains and high resistance of cysts to drugs; many agents with possible anti-amoebic activity are still being tested. In the presented study, selected chemicals are investigated in terms of their in vitro effect on corneal and environmental Acanthamoeba strains.